Sedimentology and Structural Geology of Parit Sulong, Johor - Ruslan, Nurquratul Atiqah (2016)
A geological study was carried out at Parit Sulong area, Johor which has been identified by the previous researchers as part of Payong Formation. The study area consists of three main sedimentary facies which are conglomerate facies, sandstone facies and mudstone facies. Generally, at outcrop 1 (Batu Payong), outcrop 4 (Bukit Inas) and outcrop 5 (Kampung Parit Gawong), the conglomerate facies consist of conglomerate with minor occurrence of mudstone and sandstone facies ; while at outcrop 2 (Batu Belah east), outcrop 3 (Batu Belah west) and outcrop 6 (Kia Lim Company), they consist of sandstone and sandstone facies. There are three sediment logging in total have been done over the whole localities with total bed thickness of beds ranging from 13m to 32m. There are no specific sedimentary structures have been found at each localities. Based from the laboratory analysis, the minerals in the rock samples consist of polyscystalline quartz, quartz, feldspar and carbonaceous mud clast. The depositional environment interpreted to be fluvial which is in continental system.